Distinctive Marker ‘-an’ on the Lingual Unit in Online Mass Media Diction - Heru Pratikno (Buletin Al-Turas, 2022)
PurposeThe Indonesian language continues to experience extraordinary developments as seen from its vocabularies. However, the large number of vocabularies turns often caused errors and mistakes in choosing diction pairs in an article, especially in the mass media. Therefore, this research needed to be done to classify vocabulary ending in -an based on its form, category, marker, and meaning. It was aslo intended that the vocabulary contained in the Indonesian language could be classified according to their classes.MethodThe study made use of primary data sourcing from the written language. The data came from online daily newspapers, namely pikiran-rakyat.com, republica.co.id, and mediaindonesia.com. In analyzing these data, the research applied descriptive and prescriptive qualitative methods.Result/Findings The result of the study indicated that the final form of -an in Indonesian vocabulary had certain categories, markers, and meanings. This happened because of the similarity or identical form of a word.ConclusionThe research concluded that there were word forms ending in -an functioning suffixes and someothers were part of the word itself.